Introducing HiSCoD: A new gateway for the study of historical social conflict - Cédric Chambru; Paul Maneuvrier-Hervieu (University of Zurich, Department of Economics, 2022)
Social conflict pervades human society and fulfils a number of essential functions in its development and transformation, including the creation of new norms and institutions. The Historical Social Conflict Database (HiSCoD) is an ongoing project designed to provide to scholars and society at large with a set of resources for analysing social conflict from the Middle Ages to the late 19th century. Based on original archival research and existing repositories, the aim is to provide a global database of social conflict in past societies by collecting, aggregating, documenting and harmonising data. As of today, the database contains data more than 20,000 instances of conflict, from fiscal scuffles to urban revolts involving thousands of individuals. For every event, we provide information on the date, location, type of conflict, and, when possible, number of participants, participation of women, and a summary of events. Each individual event is documented through a hierarchical system of forms using XML-EAD technology. This article describes the data collection process and presents some descriptive statistics.
Keywords: D74; H56; N00; N90; 330; Event data; sub-national; social conflict; riot; violence; protest